TRANSFORMASI STRUKTUR EKONOMI KABUPATEN INDRAGIRI HULU TAHUN 2000-2013 - Aditya Hardi Guntara; Hendro Ekwarso; Dahlan Tampubolon (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine whether there was a shift in the economic structure of the district Upstream Indragiri years 2000-2013. This study uses secondary data by collecting data by recording directly necessary data, both went to the Office of the Central Statistics Agency (BPS) of Riau Province and Upstream Indragir and undertakes a review of the literature, including books, journals, print media and scientific reports , Methods of data analysis using the Shift Share Analysis Classical and Shift Share Analysis modification of Esteban-Marquilass. The results of this study indicate that the economic structure of Upstream Indragiri district in 2000-2013 began to experience transformation from the primary sector to the secondary and tertiary sectors, although the level of friction is relatively small, but the structure of the economy from year to year, the agricultural sector still provides a major contribution to total GDP District Upstream Indragiri overall. Economic sectors in the district Upstream Indragiri yet has two advantages at once, but there are economic structures which have one of the two advantages, namely the sectors of processing industry and sector of electricity, gas and water supply with a competitive advantage, while the agricultural sector and the mining sector has the advantage of specialization.Keywords :Transformation structure, GDRP, Shift Share, Base Sector, Government Policy